Indirect tax administration efficiency of the Royal Malaysian Customs Department / Nur Azhari Mutahar and Nadiah Abd Hamid - Mutahar, Nur Azhari; Abd Hamid, Nadiah (Universiti Teknologi MARA, Perlis, 2022)
The method used to measure indirect tax administration efficiency is crucial; hence, this study will examine indirect tax administration efficiency using the cost-revenue ratio. Malaysia had experienced several changes in its indirect tax system where the shift of Malaysia’s indirect tax regime is linked to the efficiency of indirect tax administration. However, the lack of empirical research on this matter urges the current study to determine the trend of indirect tax administration efficiency level under the RMCD. In this study, secondary data were obtained from RMCD Annual Report, Ministry of Finance’s Federal Government Estimated Revenue Report, Budget Report, and Treasury Annual Report to examine the trend of RMCD’s tax administration efficiency level for 7 years (2013-2019). Both administration costs and total tax revenue collection were found to affect the efficiency level of the Royal Malaysian Customs Department (RMCD); however, there is no strong evidence to claim that administration costs indeed influence the total indirect tax revenue collection and vice-versa. Research findings and initial inputs from the RMCD Annual Reports are analysed to discuss and provide recommendations for future research works. The research findings provide important information for the RMCD and policymakers in improvising indirect tax administration.